ABDI DALEM DI PESANTREN: STUDI FENOMENOLOGI TENTANG MAKNA HIDUP SANTRI YANG MENGABDI PADA KIAI - Iqbal Hamdan Habibi (FAJAR Jurnal Pendidikan Islam, 2024)
Abdi dalem is a santri who dedicates themselves to serving a kiai at a pesantren (Islamic boarding school). This study aims to identify the psychological phenomena experienced by abdi dalem during their service period and to understand their perception of the meaning of life. The qualitative research method with a phenomenological approach, involving abdi dalem from the Hidayatul Mubtadi’ien Ngunut Tulungagung pesantren as the main subjects. Data collection techniques include semi-structured interviews, participant observation, and documentation. The results of the study reveal four main phenomena: emotional turmoil, concern for the kiai, commitment, and life lessons in the form of patience and sincerity. For the abdi dalem, the meaning of life is surrender to God, focusing on current duties with the hope of gaining blessings in the future. This study contributes to Islamic studies, particularly in pesantren and religious studies, by linking them to social and psychological aspects